Ilots bilingues et méso-alternance - Gabriela Steffen; Audrey Freytag Lauer (Recherches en didactique des langues et des cultures)
Bilingual sequences constitute a particular format of bilingual education providing sequences of a content subject in L2. They require to reflect upon language alternation: Which themes to choose? When to insert them? Which activities to plan in L2 or L1? Based on semi-structured interviews with the teachers and filmed classroom interactions, combined with the analysis of the used teaching materials, this contribution focusses on the bilingual sequences of two secondary school teachers in a Swiss German region. These sequences of geography in English L2 and history in French L2 present various forms of didactic alternation or meso-alternation understood as a form of translanguaging.